Stunting dan Upaya Pencegahannya di Kabupaten Lingga - Nabila, Shalihatun (Jurnal Empirika, 2024)
This study aims to identify cultural factors that cause stunting and prevention efforts in Lingga Regency. Stunting, a form of growth faltering, certainly impacts the quality of health development in a country, including Indonesia. For this reason, it is essential to make various efforts to accelerate the reduction of stunting carried out in multiple regions, especially the Lingga Regency. This study used a qualitative approach, collecting data through interviews. The findings of this study show that cultural factors that cause stunting are the most basic. There are still parents or mothers whose parenting patterns are traditional. Efforts have been made to prevent and overcome the problem of stunting, namely through the Healthy Kitchen to Overcome Stunting (DASHAT) Program. The Lingga Regency Health Office carries out this program and collaborates with Health Cadres to reduce stunting in Lingga Regency.